2021
DOI: 10.1007/s10879-021-09524-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Resources in a Population of Hemodialysis Patients: A New Approach to Improve Quality of Care

Abstract: Hemodialysis patients constitute a vulnerable population. Their health needs are considerable and they often present psychological symptoms such as depression and anxiety. Empirical studies have demonstrated the efficacy of positive psychology interventions to enhance the well-being of patients and alleviate their depressive symptoms. One such intervention consists in identifying and mobilizing patient resources to activate their recovery. An intervention of the sort was implemented in Switzerland with hemodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…At present, numerous studies have shown that the implementation of humanistic care model for patients in the recovery period of schizophrenia can effectively improve patients' self-awareness of their mental illness and their compliance with treatment, which can effectively improve their condition and social function and promote their recovery [ 9 ]. Studies by foreign scholars point out that implementing humanistic care for patients in the recovery period of schizophrenia to help them improve their living conditions and bad habits, remove adverse psychological factors, and restore their optimal state are the current goals of psychiatric clinical nursing reform [ 10 ].…”
Section: Related Workmentioning
confidence: 99%
“…At present, numerous studies have shown that the implementation of humanistic care model for patients in the recovery period of schizophrenia can effectively improve patients' self-awareness of their mental illness and their compliance with treatment, which can effectively improve their condition and social function and promote their recovery [ 9 ]. Studies by foreign scholars point out that implementing humanistic care for patients in the recovery period of schizophrenia to help them improve their living conditions and bad habits, remove adverse psychological factors, and restore their optimal state are the current goals of psychiatric clinical nursing reform [ 10 ].…”
Section: Related Workmentioning
confidence: 99%